Teachers' perceptions towards smart school : a case study in SMK. Three Rivers, Mukah, Sarawak, a pilot smart school in Malaysia - Jirin, Krakah (Universiti Malaysia Sarawak (UNIMAS), 2004)
This study tried to find out perceptions of teachers towards Smart School and the challenges that they faced teaching in Smart School. The sample chosen for this study were those teachers teaching Bahasa Melayu, English Language, Science and Mathematics from the school chosen for this study. Twenty-two open-ended questions were formulated for the interviews. The interviews were conducted in English and Bahasa Melayu in order to get comprehensive information for this study. The findings were analysed by using qualitative data that described the results based on the main responses of the interviewees. Transcripts of the interviews were used to identify and interpret teachers' perceptions towards Smart School. The results showed that teachers had positive or favourable perceptions toward Smart School. The study also showed that the challenges that teachers faced in the implementation of Smart School were large number of students in the class, facing weak students, insufficiency of computer, exam-oriented school, the use of software, attitudes of students and system failure or breakdown that sometimes occurred.